Lilium davidii extract alleviates p‑chlorophenylalanine‑induced insomnia in rats through modification of the hypothalamic-related neurotransmitters, melatonin and homeostasis of the hypothalamic-pituitary-adrenal axis. (1st January 2020) - Si, Yanpo; Wang, Lili; Lan, Jinxu; Li, Hanwei; Guo, Tao; Chen, Xiaohui; Dong, Chunhong; Ouyang, Zhen; Chen, Sui-qing
Abstract: Context: Lilium davidii var. unicolour Cotton ( Lilium genus, Liliaceae) is an edible plant and a herb used in China to alleviate insomnia. Objective: To investigate the alleviating insomnia mechanism of L. davidii (LD). Materials and methods: Wistar rats were intraperitoneally injected with p -chlorophenylalanine (PCPA) to establish an insomnia model. Rats were divided into six groups ( n = 8): Control, PCPA, Estazolam (0.5 mg/kg), LD extract in low, medium and high doses (185.22, 370.44, 740.88 mg/kg). Serum hormone levels of the HPA axis, levels of 5-HT, NE and MT, and the expression of GABAA and 5-HT1A receptors in hypothalamus were determined. Moreover, behavioural and pathological changes in the hypothalamus were evaluated. Results: After LD administration, body weight and brain coefficient increased by 2.74% and 8.22%, respectively, and the adrenal coefficient decreased by 25%, compared with PCPA group. Elevation of the serum hypothalamic-pituitary-adrenal (HPA) axis hormone CRH (11.24 ± 3.16 ng/mL), ACTH (565.87 ± 103.44 pg/mL) and CORT (44.28 ± 8.73 ng/mL) in the PCPA group was reversed after LD treatment. Furthermore, abnormal excitatory behaviour [5 min movement distance (2096.34 ± 259.51 cm), central exercise time (5.28 ± 1.08 s)] of insomnia rats in the PCPA group was also relieved. LD extract increased 5-HT and MT levels, reduced NE level in the hypothalamus, and upregulated the expression of GABAA R and 5-HT1A. Moreover, LD extract may improve the pathology of neurons in the hypothalamus. Conclusions: LD can be considered to develop health-care food or novel drugs to cope with the increasing number of insomniacs.